The Lifestyle in Hypertensive Patient : Literature Review - Dianita Putri; Riswani Tanjung; Tjutju Rumijati; Washudi Washudi (Jurnal Kesehatan Siliwangi, 2020)
ABSTRACT Hypertension is one of the degenerative diseases that has the highest incidence in Indonesia. Hypertension is an incurable disease but can only be controlled by changing lifestyles. Lifestyle is one indicator of a person's quality of life. Someone who has a healthy lifestyle will run his life by paying attention to the factors that can affect his health. This will cause a person's health level to be good. Good health makes a person's quality of life. Changes in lifestyle and low levels of healthy behavior can lead to various health problems. A healthy lifestyle is an important part in handling the incidence of hypertension. The purpose of this study is to describe the lifestyle of people with hypertension. This type of research is a descriptive study with adesign Systematic Literature Review. The conclusion from this research is that most hypertension sufferers have a relatively healthy diet by reducing salt consumption and only consuming low salt. In terms of physical activity, the majority of hypertensive sufferers have performed relatively healthy physical activities. In the aspect of smoking and drinking alcohol, many people with hypertension are not smokers and do not have the habit of drinking alcohol. In managing stress, some hypertension sufferers have not been able to manage the stress. The results of this study are expected to provide a lifestyle description so that the management of hypertension can be carried out optimally, especially lifestyle modification for people with hypertension.